2023
DOI: 10.1302/2046-3758.122.bjr-2022-0206.r1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genome-wide association study with regulatory SNP annotations identified novel candidate genes for osteoporosis

Abstract: AimsOsteoporosis (OP) is a metabolic bone disease, characterized by a decrease in bone mineral density (BMD). However, the research of regulatory variants has been limited for BMD. In this study, we aimed to explore novel regulatory genetic variants associated with BMD.MethodsWe conducted an integrative analysis of BMD genome-wide association study (GWAS) and regulatory single nucleotide polymorphism (rSNP) annotation information. Firstly, the discovery GWAS dataset and replication GWAS dataset were integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…36 Moreover, global IL-19 deletion had no effect on bone formation, but suppressed osteoclastogenesis in the LPStreated mice group. Nevertheless, we did not detect the cytokines associated with C57BL/6 mice, 41 and it remains to be further explored whether there is a decrease in cytokines such as CCL3, TNF-α, and CCL4 similar to that in BALB/c mice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…36 Moreover, global IL-19 deletion had no effect on bone formation, but suppressed osteoclastogenesis in the LPStreated mice group. Nevertheless, we did not detect the cytokines associated with C57BL/6 mice, 41 and it remains to be further explored whether there is a decrease in cytokines such as CCL3, TNF-α, and CCL4 similar to that in BALB/c mice.…”
Section: Discussionmentioning
confidence: 65%
“…In vitro experiments have shown that IL-19 inhibits osteoblast differentiation by suppressing NF-κB and 38 kD mitogen-activated protein kinases (p38MAPK) activation, as well as c-Fos expression, in the mouse macrophage-like cell line RAW264.7. 41 , 49 We examined the levels of RANKL and OPG in peripheral blood and bone marrow of two groups of mice. In the LPS-induced bone loss mouse model, there was no significant change in RANKL content in serum and femoral bone marrow suspension, but OPG content was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…7 With an ageing population, it is predicted that OP-related healthcare burdens will increase rapidly. 8 Multiple environmental and genetic factors play a role in OP, [9][10][11] but there is still an urgent need to determine more modifiable potential risk factors for OP.…”
Section: Introductionmentioning
confidence: 99%